The Potential of Public Parks for Business Activity in An Urban Community - Raja Abd Majid, Tengku Zalikha Nadrah; Anuar, Ahmad Nazrin Aris; Ramli@ Ramele, Rohaslinda; Digby Whyte, (International Journal of Sustainable Construction Engineering and Technology, 2023)
Apart from offering a positive impact on general well-being, public parks play critical roles in community and social. The previous study has always focused on the parks' effect on property values, which is quantifiable, but little is known about the profit-able value of public parks on the urban community, particularly in the context of business activity. This research aim is to discover the potential of public parks for a business activity for the community in Kuala Lumpur as a case study. Therefore, the research objectives are: i) To identify the attributes factors of business activity in public park, ii) To determine the types of business activity. The research employed a quantitative approach by distributing online questionnaires to the random urban community. Significantly, 170 respondents have responded to the questions based on the sampling method applied for the random size of the population. The findings show that park attributes are derived from the aspects of attracting the urban community to public parks and influencing business activity through community participation. The urban community prefers to have added program value as part of the park's business activity while also recognizing the value of preserving passive activities by not over-commercializing the park. The findings also show that repurposing a public park as a business district can be innovative, but it takes preparation and a suitable system from the park's management.